ANALISIS FAKTOR PENYEBAB GAGAL KIRIM PAKET MENGGUNAKAN METODE FTA DAN FMEA PADA PT XYZ - Amel Dika Fista Iamanda; Indro Kirono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the factors causing delivery failures at PT XYZ, which include delivery delays, package damage, and package loss. These issues represent the most frequent operational failures reported by customers and have the potential to reduce service quality, customer satisfaction, and the company’s competitiveness in the logistics industry. Therefore, a systematic analysis is required to identify the root causes of failures and determine appropriate improvement priorities. The research employs a descriptive-quantitative approach by integrating Fault Tree Analysis (FTA) and Failure Mode and Effects Analysis (FMEA) methods. Data were collected through field observations, interviews with operational staff, risk assessment questionnaires, and customer complaint data from 2025. The FTA method was used to map the cause-and-effect relationships leading to delivery failures, while the FMEA method was applied to assess the risk level of each failure mode based on severity, occurrence, and detection parameters, resulting in the calculation of the Risk Priority Number (RPN). The results indicate that delivery delays represent the highest-risk failure mode with an RPN value of 280, followed by package damage with an RPN of 192 and package loss with an RPN of 189. These findings suggest that delivery delays should be prioritized for corrective actions. This study concludes that the combined use of FTA and FMEA is effective in identifying root causes and prioritizing risk mitigation strategies to improve operational performance and delivery service quality